2020
DOI: 10.1002/jgc4.1282
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic uncertainties, ethical tensions, and accounts of role responsibilities in genetic counseling communication

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…These factors may lead to additional stress and frustration for both clinicians and patients 34 . Clear communication and setting expectations in pre and post‐test counseling can improve the experience and foster informed decision‐making 35–37 …”
Section: Discussionmentioning
confidence: 99%
“…These factors may lead to additional stress and frustration for both clinicians and patients 34 . Clear communication and setting expectations in pre and post‐test counseling can improve the experience and foster informed decision‐making 35–37 …”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we draw on theme‐oriented discourse analytic approach (TODA) (Roberts & Sarangi, 2005), which has been widely employed in previous empirical research on communication in genetic counseling and other healthcare settings (Hammerstad et al., 2020; Sarangi, 2010; Shipman et al., 2014; Zayts et al., 2019; Zayts‐Spence et al., 2021). The focal theme of investigation in this study is elicitation of children's understanding of genetic information.…”
Section: Methodsmentioning
confidence: 99%
“…Through repeated readings of the transcripts of the interactions (Roberts & Sarangi, 2005), the first and the second authors identified key junctures in the interactions where elicitations of children's understanding of provided information occurred. Following that, the first and the second authors examined recurrent communicative strategies employed by the counselors to elicit children's understanding (Hammerstad et al., 2020; Sarangi, 2010). The first and the second author worked independently and then checked the identified junctures in the interactions and the strategies for congruence.…”
Section: Methodsmentioning
confidence: 99%
“…Así, los rasgos característicos de cada raza se heredan con ciertos grados de variación entre individuos, sin embargo, la genética de cada población también está sujeta a factores que la modifican, como la selección natural, las mutaciones y los polimorfismos (36). De esta forma, las diferencias biológicas entre los seres humanos pueden estar condicionadas por la interacción entre el genoma y el ambiente (37).…”
Section: Persona Libertad Y Responsabilidadunclassified